Self-reported health, physical activity and prevalence of complaints in elite cross-country skiers and matched controls - Alricsson, M.; Werner, S. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to compare physical health, physical activity and location for possible symptoms in high school students with cross-country skiers of the same age from ski high schools. Another aim was to study back pain with regards to influence on skiing. Methods: The subjects studied were: 92% (n=120) of all Swedish cross-country skiers at ski high schools and 68% (n=993) of regular high school students from the North part of Sweden answered a reliable questionnaire (r=1) with regards to health, physical activity and location of possible symptoms/injuries during the last 3 months. Furthermore, the skiers answered questions on possible ski related back pain. Results: All skiers were active also in other sports compared with 26% of the controls and at considerably higher levels of physical effort than the controls; 92% of the skiers and 76% of the controls described themselves as healthy, meaning ''very good'' or ''good'' (P=0.0001); 55% of the skiers and 64% of the controls reported recent symptoms (P=0.06); 47% of the skiers reported previous or present complaints of back pain, mainly low back pain, which could be relieved by changing body position from a flexed to a more extended one while skiing, and 77% reported their back pain to disappear during rest. Conclusion: These results show the need for encouraging regular high school students to participate in sport. It also shows the importance of introducing preventative strategies regarding back pain to long-distance cross-country skiers, who are exposed to a prolonged flexed position of their back.